Board Diversity and Value of Listed Industrial Goods Firms in Nigeria: Does Audit Committee Independence Matter? - Bawa, Junaidu; Aruwa, Suleiman A.S.; Mamman, Suleiman; Almustapha, Sadiya Ahmed (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
This study investigates the effect of board diversity specifically gender, nationality, and expertise on the firm value of listed industrial goods firms in Nigeria, with a focus on the moderating role of audit committee independence. Using panel data from 11 firms spanning 2014 to 2023, and employing panel regression analysis, the findings reveal that board gender diversity and board expertise significantly enhance firm value. Moreover, audit committee independence strengthens the positive effects of gender diversity and expertise on firm performance. However, board nationality diversity shows no significant direct or moderate influence on firm value. These results underscore the importance of inclusive and skilled boards, supported by independent audit oversight, in improving firm outcomes. The study suggests among others that the regulatory bodies such as the Financial Reporting Council (FRC) and the Nigerian Exchange Group (NGX) should enforce minimum female representation on boards to institutionalize the benefits of gender diversity.